Dilated Superior Ophthalmic Vein: Clinical and Radiographic Features of 113 Cases. Issue 1 (January 2018) - Adam, Christopher R.; Shields, Carol L.; Gutman, Justin; Kim, H. Joon; Hayek, Brent; Shore, John W.; Braunstein, Alexandra; Levin, Flora; Winn, Bryan J.; Vrcek, Ivan; Mancini, Ronald; Linden, Craig; et al.
Abstract : Purpose: Dilated superior ophthalmic vein (SOV) is an uncommon radiographic finding. The authors review the presentation, etiology, radiography, and visual implications of 113 patients with dilated SOV. Methods: An observational case series and multicenter retrospective chart review were conducted. There were 113 patients with a dilated SOV. Outcome measures included patient demographics, clinical features, radiographic findings, diagnosis, and treatment, and treatment outcomes were assessed. Results: Cases included 75 women (66%) and 38 men (34%) with a mean age of 49 ± 24 years (range, 0.4–90 years). Diagnoses fell under 6 categories: vascular malformation (n = 92, 81%), venous thrombosis (n = 11, 10%), inflammatory (n = 6, 5%), traumatic hemorrhage (n = 2, 2%), lymphoproliferative (n = 1, 1%), and infectious (n = 1, 1%). Imaging modalities utilized included MRI (n = 98, 87%), digital subtraction angiography (n = 77, 68%), CT (n = 29, 26%), and ultrasonography (n = 4, 4%). Disease status at last follow up included no evidence of disease (n = 57, 50%), alive with persistent disease (n = 53, 47%), and expired from disease (n = 3, 3%). Treatment and management was tailored to the underlying disease process with a mean follow up of 18 months (range, 1 day to 180 months). Visual impairment observed at presentation and last follow up across all cases was 26% and 22%, respectively. Conclusion: Dilated SOV is a rare radiographic finding resulting from a wide spectrum of etiologies with clinical implications ranging from benign to sight- and life-threatening. Dilated SOV is most often found with dural-cavernous fistula or carotid-cavernous fistula, orbital or facial arteriovenous malformation, and venous thrombosis. Recognition of this finding and management of the underlying condition is critical. Abstract : A retrospective review of 113 cases of dilated superior ophthalmic vein on radiography was conducted. Most common etiologies were arteriovenous fistula (63%) and arteriovenous malformation (19%). Patient demographics, clinical manifestations, etiologies, radiographic characteristics, and visual implications were described.